The Influence of the Traditional Game "Mpa’a Gopa" on Elementary School Students’ Interpersonal Intelligence - Firdaus, Firdaus; Satriawan, Rabwan; Irawan, Ewan (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aims to determine the effect of the traditional game ‘Mpa’a Gopa’ on the interpersonal intelligence character values of primary school students, which includes three main aspects: focus, cooperation, and strategy. Materials and methods. A quasi-experimental quantitative method with a one-group pretest-posttest design was used. The subjects were 15 students, 8 girls and 7 boys aged 12-13 years. The instrument used was a questionnaire about the effectiveness of the ‘Mpa’a Gopa’ game, which had undergone validity testing with all items declared valid (calculated r > table r) and reliability testing with a Cronbach’s Alpha value of 0.873, which is considered reliable. Data collection was conducted using a pretest-posttest method through the application of the ‘Mpa’a Gopa’ game. Data analysis used descriptive statistics, the Shapiro-Wilk normality test, and a paired t-test with the help of SPSS 25. Results. Descriptive analysis results showed an increase in the average score of the application of ‘Mpa’a Gopa’ in the aspect of cooperation from 61.20 to 79.33, the aspect of focus from 63.47 to 77.67, and the aspect of strategy from 61.73 to 78.20. The Shapiro-Wilk normality test results showed a sig value of 0.200 > 0.05, meaning that the data was normally distributed. The results of the paired sample t-test showed a t-count of 20.56 (cooperation), 14.77 (focus), 17.75 (strategy) with a sig of 0.000 < 0.05, which means there is a significant difference between the pretest and posttest scores. Conclusion. The traditional game of ‘Mpa’a Gopa’ has been proven to have a significant effect on improving the interpersonal intelligence of fifth-grade students at SDN Inpres Teke, particularly in terms of their ability to cooperate, maintain focus, and develop strategies.